2018
DOI: 10.1371/journal.pone.0196209
|View full text |Cite
|
Sign up to set email alerts
|

Beyond syndromic management: Opportunities for diagnosis-based treatment of sexually transmitted infections in low- and middle-income countries

Abstract: IntroductionIn light of the limited impact the syndromic management approach has had on the global sexually transmitted infection (STI) epidemic, we assessed a care model comprising point-of-care (POC) STI testing, immediate treatment, and expedited partner therapy (EPT) among a cohort of young women at high HIV risk in South Africa.Methods and findingsHIV negative women presenting for STI care underwent POC testing for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 34 publications
1
95
0
5
Order By: Relevance
“…The utility of GeneXpert has been evaluated in remote populations such as an aboriginal community in Australia ; in routine antenatal care in Papua New Guinea (with STI rates by GeneXpert of CT 20%, NG 11.2% and TV 37.6%) ; in HIV‐infected pregnant women in South Africa (40.2% with STIs) . Another utility study in South Africa in HIV‐negative women presenting for STI care or with symptoms (CT 18.4%, NG 5.2%, TV 3%) resulted in STI testing of symptomatic and asymptomatic women and the same‐day treatment, with expedited partner treatment and reduced reinfection after six months . A study in Rwanda has shown that integrating POCTs for BV, TV (OSOM) and CT/NG (GeneXpert) in women with urogenital symptoms and increased risk of STIs has improved diagnostic accuracy, with moderate sensitivity and high specificity for CT/NG/TV compared with using syndromic management, and has remarkably reduced overtreatment .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The utility of GeneXpert has been evaluated in remote populations such as an aboriginal community in Australia ; in routine antenatal care in Papua New Guinea (with STI rates by GeneXpert of CT 20%, NG 11.2% and TV 37.6%) ; in HIV‐infected pregnant women in South Africa (40.2% with STIs) . Another utility study in South Africa in HIV‐negative women presenting for STI care or with symptoms (CT 18.4%, NG 5.2%, TV 3%) resulted in STI testing of symptomatic and asymptomatic women and the same‐day treatment, with expedited partner treatment and reduced reinfection after six months . A study in Rwanda has shown that integrating POCTs for BV, TV (OSOM) and CT/NG (GeneXpert) in women with urogenital symptoms and increased risk of STIs has improved diagnostic accuracy, with moderate sensitivity and high specificity for CT/NG/TV compared with using syndromic management, and has remarkably reduced overtreatment .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, syndromic management provides an entry point for STI management and control. However, there are clearly limitations to the syndromic approach for the management of STIs, the likely impact on the control of STIs and the link with AMR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many programmes among FSWs in resource‐limited settings currently rely on syndromic management of STIs, and given that the majority of STIs are asymptomatic, this approach is likely to result in untreated STIs and ongoing transmission . To uphold improvements in SRHR through integrated PrEP delivery, there is demonstrated need to invest in improvements for STI services, including low‐cost point‐of‐care STI tests where possible , vaccination for human papilloma virus and viral hepatitis, and other modalities for STI management .…”
Section: Discussionmentioning
confidence: 99%
“…Trichomonas vaginalis'in (T. vaginalis) ürogenital insanda sisteme yerleşmesiyle oluşan hastalığa Trichomoniasis denir. Dünyada viral olmayan seksüel geçişli hastalıklar arasında ilk sırada, en yaygın görülen vajinit etkenleri arasında da üçüncü sırada yer almaktadır (1)(2)(3)(4)(5). Bulaşım cinsel yolla olmakta birlikte, daha az sıklıkla tuvalet eşyası, yüzme havuzları ve alafranga tuvaletlerle de olabileceği bilinmektedir.…”
Section: Introductionunclassified